2014
DOI: 10.1111/jomf.12113
|View full text |Cite
|
Sign up to set email alerts
|

A Population‐Based Study of Alcohol Use in Same‐Sex and Different‐Sex Unions

Abstract: The present study advances research on union status and health by providing a first look at alcohol use differentials among different-sex and same-sex married and cohabiting individuals using nationally representative population-based data (National Health Interview Surveys 1997–2011, N = 181,581). The results showed that both same-sex and different-sex married groups reported lower alcohol use than both same-sex and different-sex cohabiting groups. The results further revealed that same-sex and different-sex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 78 publications
(40 citation statements)
references
References 102 publications
(190 reference statements)
3
37
0
Order By: Relevance
“…The present study used data from the pooled NHIS to examine differences in a wide range of children’s physical and mental well-being outcomes within and across households headed by same-sex and different-sex married and cohabiting couples. The NHIS is one of the first nationally representative studies identifying children in families headed by two parents of the same sex who are married or cohabiting (Reczek et al 2014). The first goal of the study is to test whether the child health advantage of parental marriage differs across families headed by different-sex and same-sex married and cohabiting parents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study used data from the pooled NHIS to examine differences in a wide range of children’s physical and mental well-being outcomes within and across households headed by same-sex and different-sex married and cohabiting couples. The NHIS is one of the first nationally representative studies identifying children in families headed by two parents of the same sex who are married or cohabiting (Reczek et al 2014). The first goal of the study is to test whether the child health advantage of parental marriage differs across families headed by different-sex and same-sex married and cohabiting parents.…”
Section: Discussionmentioning
confidence: 99%
“…The NHIS is the most appropriate population-based data set available for this endeavor, and it has been effectively used in research on same-sex family structure and adult health (Denney et al 2013; Liu et al 2013; Reczek et al 2014; Ward et al 2014). In particular, the ability to identify same-sex and different-sex cohabiting and married family structures via a household survey is a critical step forward in this research area, especially given the wide array of developmental outcomes among children to which these family structures can be linked in these data.…”
Section: Introductionmentioning
confidence: 99%
“…According to fundamental cause theory, the health disparities of gay and lesbian individuals are due, in part, to social stigma and historically unequal access to legal and institutional benefits of marriage that contribute to socioeconomic disadvantage; socioeconomic disadvantage is in turn associated with increased stress, psychological distress, and worse self-rated health (Hatzenbuelher, McLaughlin, Keyes, & Hasin, 2010; Meyer, 2003a,b). Several studies show that SES also appears to play a role in differences between same-sex cohabiting couples and their different-sex married and cohabiting counterparts on both self-rated health and health behavior (Denney et al, 2013; Liu et al, 2013; Reczek, Liu, & Brown, 2014; Reczek, Liu, & Spiker, 2014). For example, Liu and colleagues found that the same-sex cohabiting were disadvantaged in health relative to the different-sex married, but that the same-sex cohabiting’s higher SES actually protected them from even worse relative self-rated health.…”
Section: Socioeconomic Statusmentioning
confidence: 99%
“…Existing data sources have a number of issues in identifying sexual minorities, and the NHIS is no exception. Still, many scholars have used the NHIS to examine same-sex families, articulating the challenges and rewards of this endeavor (e.g., Denny et al 2013; Liu et al 2013; Reczek et al 2014; Ward et al 2014). With previously identified data challenges in mind, we took special care in our Demography article to note known data limitations as best as possible.…”
Section: The National Health Interview Surveymentioning
confidence: 99%